Analisis Wacana Kritis Pada Meme Politik Terkait Wacana Kenaikan Pajak Yang Mencekik di Media Sosial: Analisis Wacana Kritis, Meme Kenaikan Pajak yang Mencekik, Media Sosial - Wahyuni, Sry Wahyuni (Linguistik, Terjemahan, Sastra (LINGTERSA), 2025)
The title of this research is “Critical Discourse Analysis on Political Memes related to the Discourse on Strangling Tax Hikes on Social Media”. This research aims to analyze the text dimensions of political memes regarding tax increases on social media using the Critical Discourse Analysis (AWK) approach of Teun A. Van Dijk’s model. This approach includes three main structures, namely macro structure, superstructure, and micro structure. The research used qualitative methods with data collection techniques through online observation and documentation. The data sources consist of five political memes taken from Instagram, Facebook, and X (Twitter), and are supported by official documents and mass media articles. The results show that in the macro structure, the main themes that emerge in the memes include criticism of the tax increase policy that is considered burdensome to the people, the 12% VAT burden, and a comparison with the obligation of zakat in Islamic teachings. The government is portrayed as if it is blackmailing the people through these fiscal policies. In the superstructure, varied schematic patterns were found, where most memes followed the flow of the title, main idea, and supporting ideas, while others did not fully follow the scheme. On the microstructure, the analysis identified the use of various stylistics, such as satire, hyperbole, rhetoric, comparison, and irony. Some memes utilize visual stylistics without explicit lingual elements but still convey sharp criticism of the government. This study concludes that political memes act as a medium of expression of social criticism of tax policy in Indonesia, represent public dissatisfaction, and show the economic inequality felt by the public.